Dampak Judi Online terhadap Keharmonisan Rumah Tangga dalam Perspektif Hukum Keluarga Islam di Kecamatan Topos Kabupaten Lebong - Victor Pratama Mandala Putra; Ilda Hayati; Mabrur Syah; Rifanto Bin Ridwan (Mutawasith: Jurnal Hukum Islam, 2026)
This phenomenon constitutes a serious concern within Muslim families, as marital harmony represents a fundamental pillar in Islamic family law. Accordingly, this study seeks to identify the underlying factors that position online gambling as a threat to household stability, to examine its impact on marital harmony among Muslim families in Kecamatan Topos, and to analyze the responses offered by Islamic family law in addressing this issue. This research adopts a qualitative descriptive approach within a field research design. Data were collected through in-depth interviews with 20 informants, comprising 10 household heads involved in online gambling, 5 wives, 3 religious leaders, and 2 Islamic counselors. Data collection techniques included interviews, observation, and documentation, which were subsequently analyzed using thematic analysis framed by fiqh al-usrah and maqashid syariah perspectives. The findings indicate that the primary contributing factors include economic pressure, ease of digital access, and psychological addiction, all of which lead to the neglect of familial responsibilities. The resulting impacts involve financial conflicts, strained marital relations, declining communication quality, and child neglect. From the standpoint of Islamic family law, such practices are categorized as mafsadah and may be construed as forms of nusyuz or dharar.